Strain rate and microtexture analysis of rapid-quenched AA6061 friction stir welds produced with tool eccentricity - Luqman Hakim, Ahmad Shah; Hou, Wentao; Razmpoosh, Mohammad Hadi; Walbridge, Scott S.; Gerlich, Adrian P. (Elsevier Editora Ltda, 2022)
The paper investigates the effect of tool eccentricity on the strain rate and microtextures produced in rapid-quenched AA6061 friction stir welds. Thermocouples are embedded in the tool and the thermal cycle are recorded via a data acquisition system. Stir zone grain refinement is observed in all samples, with the eccentric sample having the finest grains (3.18 μm). The strain rate is measured to be between 0.17 and 51.94 s-1, with the eccentric sample experiencing the highest strain rate. The pole figures indicate crystallographic textures shifted approximately 90° when tool eccentricity is employed. The aligned samples have a strong {11-2}[removed] B simple shear texture component, while the eccentric sample shows morphological changes towards a strong {11-1}[removed] A simple shear texture component.